Erythrocyte-derived liposomes for the treatment of inflammatory diseases. (24th August 2022) - Olival, A.; Vieira, S. F.; Gonçalves, V. M. F.; Cunha, C.; Tiritan, M. E.; Carvalho, A.; Reis, R. L.; Ferreira, H.; Neves, N. M.
Abstract: Effective and safe therapies to counteract persistent inflammation are necessary. We developed erythrocyte-derived liposomes (EDLs) with intrinsic anti-inflammatory activity. The EDLs were prepared using lipids extracted from erythrocyte membranes, which are rich in omega-3 fatty acids with several health benefits. Diclofenac, a widely used anti-inflammatory drug, was incorporated into EDLs in relevant therapeutic concentrations. The EDLs were also functionalised with folic acid to allow their active targeting of M1 macrophages, which are key players in inflammatory processes. In the presence of lipopolysaccharide (LPS)-stimulated macrophages, empty EDLs and EDLs incorporating diclofenac were able to reduce the levels of important pro-inflammatory cytokines, namely interleukin-6 (IL-6; ≈85% and 77%, respectively) and tumour necrosis factor-alpha (TNF-α; ≈64% and 72%, respectively). Strikingly, cytocompatible concentrations of EDLs presented similar effects to dexamethasone, a potent anti-inflammatory drug, in reducing IL-6 and TNF-α concentrations, demonstrating the EDLs potential to be used as bioactive carriers in the treatment of inflammatory diseases.